2021
DOI: 10.1101/2021.02.09.430400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shadow ORFs illuminated: long overlapping genes inPseudomonas aeruginosaare translated and under purifying selection

Abstract: The existence of overlapping genes (OLGs) with significant coding overlaps revolutionises our understanding of genomic complexity. We report two exceptionally long (957 nt and 1536 nt), evolutionarily novel, translated antisense open reading frames (ORFs) embedded within annotated genes in the medically important Gram-negative bacterium Pseudomonas aeruginosa. Both OLG pairs show sequence features consistent with being genes and transcriptional signals in RNA sequencing data. Translation of both OLGs was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 126 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…The unusual sequence characteristics of long overlapping CDSs may have also contributed to the difficulty of their discovery, resulting in undercounting 40 , 41 . One reason put forward to explain why long nested overlaps should be rare includes the evolutionary burden of maintaining larger overlaps, although evidence to the contrary showing positive selection at overlaps 27 , 42 , 43 shows that this explanation may be too simplistic. Selection for long convergent overlaps has been shown to have a strong reading frame bias and it has been suggested that retention involves positive selection at the birth of the overlap, followed by purifying selection afterwards 27 .…”
Section: Overlapping Gene Topology and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual sequence characteristics of long overlapping CDSs may have also contributed to the difficulty of their discovery, resulting in undercounting 40 , 41 . One reason put forward to explain why long nested overlaps should be rare includes the evolutionary burden of maintaining larger overlaps, although evidence to the contrary showing positive selection at overlaps 27 , 42 , 43 shows that this explanation may be too simplistic. Selection for long convergent overlaps has been shown to have a strong reading frame bias and it has been suggested that retention involves positive selection at the birth of the overlap, followed by purifying selection afterwards 27 .…”
Section: Overlapping Gene Topology and Functionmentioning
confidence: 99%
“…Selection for long convergent overlaps has been shown to have a strong reading frame bias and it has been suggested that retention involves positive selection at the birth of the overlap, followed by purifying selection afterwards 27 . Recently, an overlapping protein-encoding CDS with extensive 603 bp overlap has been discovered embedded in the highly conserved ompA gene in enterohaemorrhagic Escherichia coli 44 , showing that, with improved measurement tools, more of these long nested overlaps may be discovered 42 .…”
Section: Overlapping Gene Topology and Functionmentioning
confidence: 99%
“…An apparent scenario would be an emergence through overprinting ( 63 ) after the split of the Escherichia / Shigella clade. Interestingly, many of recently characterized overlapping genes are taxonomically restricted and were suggested being orphans ( 21 , 22 , 24 , 25 ). Orphans presumably code for non-essential, specialized functions that benefit the particular organism.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies provided strong indications for the existence of long overlapping genes in bacteria ( 10 , 19 , 20 ). In addition, evidence for the functionality of non-trivial overlapping genes in bacteria is accumulating ( 3 , 21 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, frequently the evidence provided is partial, the function of one or both overlapped genes is unknown, or is not clear whether the corresponding mRNA is transcribed and translated into protein. More frequently, the regulation regime of the proteins expressed and their functions are unknown (Kreitmeier et al, 2022). The historic case of overlapped genes in phage ϕX174 (Sanger et al, 1977) has been updated recently.…”
Section: Introductionmentioning
confidence: 99%